63.3k views
2 votes
2x^2+3x=(2x-1)(x+1)
Pls do explain

User Jiho Choi
by
5.1k points

2 Answers

3 votes
X= -1/2 hope this helps hehe :)
User Remco Ros
by
4.4k points
4 votes

Answer:


x=-(1)/(2)

Explanation:

You could solve this problem by either: Factoring or by using the Quadratic Formula.

SOLVING BY FACTORING STEPS

STEP 1: Move (2x−1)(x+1) to the left side of the equation by subtracting it from both sides.


2x^2+3x-(2x-1)(x+1)=0

STEP 2: Simplify 2x^2+3x−(2x−1)(x+1).


2x+1=0

STEP 3: Simplify each term.


2x^2+3x-2x^2-x+1=0

STEP 4: Simplify by adding terms.


2x+1=0

STEP 5: Subtract 1 from both sides of the equation.


2x=-1

STEP 6: Divide each term by 2 and simplify.


x=-(1)/(2)

SOLVE BY USING THE QUADRATIC FORMULA STEPS

STEP 1: Move all terms to the left side of the equation and simplify.


2x+1=0

STEP 2: Subtract 1 from both sides of the equation.


2x=-1

STEP 3: Divide each term by 2 and simplify.


x=-(1)/(2)

User Akos Krivachy
by
4.2k points